The Effect of Leadership Style, Rotation and Motivation on Performance (Literature Review) - Wage Rinanto (Dinasti Publisher, 2023)
The Literature Review article on the Influence of Leadership Style, Rotation and Motivation on Performance is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of Human Resource Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this literature review article are: 1) Leadership Style influences Performance; 2) Rotation has an effect on Performance; and 3) Motivation influences performance.